Exploring client violence during home visits: a qualitative study of perceptions and experiences of Israeli nurses - Yael Sela; Keren Grinberg; Inbal Halevi Hochwald (BMC, 2024)
Abstract Background Home care provides an excellent opportunity for personalizing treatment as nurses see patients in their natural environment. Along with its many advantages, the home care environment carries unique risks, as nurses are usually alone, without the protection and security provided by primary care clinics. There are no accurate data in Israel on the scope and characteristics of client violence against nurses during home visits. We conducted a qualitative study to investigate the nature of client violence faced by Israeli nurses during home visits, to gain insights into their perceptions and experiences, and to contribute to the development of effective policies and strategies to combat client violence in the healthcare sector. Methods Twenty-seven female nurses from primary care clinics, who were exposed to client violence during a home visit, were interviewed using a semi-structured interview guide. The interviews were transcribed and analyzed, and categories and themes were extracted. Results Most nurses interviewed experienced at least three incidents of client violence, the most common of which was verbal abuse. The nurses perceived that the location of the encounter between the nurse and the patient in the patient's natural surroundings, rather than within the controlled boundaries of a clinic, contributes to the risk of violence. Violence affected the nurses' professional decisions. The nurses reported that their organization had no established guidelines or instructions for safely conducting home visits, they were not provided with protective or security measures for emergencies, nor did they perceive that they had sufficient training to deal with client violence in clients' homes. Conclusions Nurses encounter a range of challenges that make it difficult for them to deal with client violence during home visits, affecting their personal safety and professional decisions. Their ability to manage such situations is shaped by a complex interplay of personal and organizational factors and requires a range of strategies and resources to effectively address them.